HEREDITARY ENDOCRINE TUMOURS: CURRENT STATE-OF-THE-ART AND RESEARCH OPPORTUNITIES: History of the multiple endocrine neoplasia workshops and overview of MEN2019. Issue 8 (August 2020) - Grubbs, Elizabeth; Halperin, Daniel; Waguespack, Steven G; Gagel, Robert F
Abstract : The multiple endocrine neoplasia (MEN) workshops had their beginnings at Queen's University in Kingston, Ontario in June 1984. This initial meeting brought clinicians and scientists together to focus on mapping the gene for multiple endocrine neoplasia type 2 (MEN2). These efforts culminated in the identification of the RET protooncogene as the causative gene a decade later. Over the next 35 years there were a total of 16 international workshops focused on the several MEN syndromes. Importantly, these workshops were instrumental in efforts to define the molecular basis for multiple endocrine neoplasia type 1 (MEN1), MEN2, von Hippel-Lindau disease (VHL), Carney Complex, hereditary pheochromocytoma and hyperparathyroidism. In this same spirit some 150 scientists and clinicians met at MD Anderson Cancer Center, 27–29 March 2019, for the 16th International Workshop on Multiple Endocrine Neoplasia (MEN2019). Appropriate to its location in a cancer centre, the workshop focused on important issues in the causation and treatment of malignant aspects of the MEN syndromes: medullary thyroid carcinoma, pancreatic neuroendocrine tumours, malignant pheochromocytoma and parathyroid carcinoma. Workshops at the meeting focused on a better understanding of how the identified molecular defects in these genetic syndromes lead to transformation, how to apply targeted kinase inhibitors and immunotherapy to treat these tumours and important clinical management issues. This issue of Endocrine-Related Cancer describes these discussions and recommendations.